Essential Oils as Alternatives for Root-Canal Treatment and Infection Control Against Enterococcus faecalis—A Preliminary Study - Monica Cristina Nagy-Bota (Applied Sciences, 2021)
Since natural alternatives are needed in dentistry for the treatment of root canal, where the standard irrigant is NaOCl with significant toxicity, the aim of the study was to assess the antibacterial properties of non-chemical root-canal irrigants (aqueous extracts of oregano, thyme, lemongrass, melaleuca and clove essential oils) against Enterococcus faecalis. For this, aqueous extracts of each essential oil (AqEO) were prepared. A solution of sodium hypochlorite (NaOCl) was used as a positive standard against which the antimicrobial effects of AqEO could be reported. The root canals of seven teeth were inoculated with 20 µL of Enterococcus faecalis ATCC29212 inoculum and incubated overnight at 37 °C. All the teeth canals were instrumented and were irrigated with the corresponding AqEO, NaOCl and saline solution, then rinsed with saline. Bacteriological samples for each canal post-instrumentation were collected with sterile paper points which were inoculated on culture media. A second processing followed the same methodology but involved only irrigation and no instrumentation. Using instrumentation, thyme and clove completely inhibited Enterococcus faecalis growth. Without instrumentation, clove and oregano AqEOs completely reduced the bacterial load as seen in direct inoculation, but bacterial growth was observed in all the samples after enrichment, except for NaOCl. Nevertheless, the turbidity of the enrichment media was lower for the samples irrigated with AqEOs than for control. In conclusion, AqEOs of thyme, oregano and clove showed a promising antibacterial effect, especially when teeth instrumentation was performed.